Jean Piaget e Paulo Freire respeito mútuo, autonomia moral e educação - Alves, Sabrina Sacoman Campos (Editora Oficina Universitária, 2022)
The research presented in this book is the result of a professional and academic path that has allowed us to look hopefully at education and social reality. Believing in the transforming possibility of education and, therefore, in the ability of men and women to build a more just and humane society for all, we seek to verify what are the similarities between the theories of Jean Piaget and Paulo Freire, regarding aspects of moral development, and analyze the implications of these approaches for educational theory and practice. Always considering that education aims at autonomy and trains subjects capable of acting and thinking about reality, in a critical and more humane way.